Measuring hepatic functional reserve using low temporal resolution Gd-EOB-DTPA dynamic contrast-enhanced MRI: a preliminary study comparing galactosyl human serum albumin scintigraphy with indocyanine green retention. - Saito, Kazuhiro; Ledsam, Joseph; Sourbron, Steven; Hashimoto, Tsuyoshi; Araki, Yoichi; Akata, Soichi; Tokuuye, Koichi (European Radiology, 2014)
Objective: To investigate if tracer kinetic modelling of low temporal resolution dynamic contrast-enhanced (DCE) MRI with Gd-EOB-DTPA could replace technetium-99 m galactosyl human serum albumin (GSA) single positron emission computed tomography (SPECT) and indocyanine green (ICG) retention for the measurement of liver functional reserve.Methods: Twenty eight patients awaiting liver resection for various cancers were included in this retrospective study that was approved by the institutional review board. The Gd-EOB-DTPA MRI sequence acquired five images: unenhanced, double arterial phase, portal phase, and 4 min after injection. Intracellular contrast uptake rate (UR) and extracellular volume (Ve) were calculated from DCE-MRI, along with the ratio of GSA radioactivity of liver to heart-plus-liver and per cent of cumulative uptake from 15-16 min (LHL15 and LU15, respectively) from GSA-scintigraphy. ICG retention at 15 min, Child-Pugh cirrhosis score (CPS) and postoperative Inuyama fibrosis criteria were also recorded. Statistical analysis was with Spearman rank correlation analysis.Results: Comparing MRI parameters with the reference methods, significant correlations were obtained for UR and LHL15, LU15, ICG15 (all 0.4-0.6, P < 0.05); UR and CPS (-0.64, P < 0.001); Ve and Inuyama (0.44, P < 0.05).Conclusion: Measures of liver function obtained by routine Gd-EOB-DTPA DCE-MRI with tracer kinetic modelling may provide a suitable method for the evaluation of liver functional reserve.Key Points: • Magnetic resonance imaging (MRI) provides new methods of measuring hepatic functional reserve. • DCE-MRI with Gd-EOB-DTPA offers the possibility of replacing scintigraphy. • The analysis method can be used for preoperative liver function evaluation.